The development of sensorimotor influences in the audiovisual speech domain: some critical questions - Guellaï, Bahia; Streri, Arlette; Yeung, H. Henny (Frontiers in Psychology, 2014)
Speech researchers have long been interested in how auditory and visual speech signals are integrated, and the recent work has revived interest in the role of speech production with respect to this process. Here, we discuss these issues from a developmental perspective. Because speech perception abilities typically outstrip speech production abilities in infancy and childhood, it is unclear how speech-like movements could influence audiovisual speech perception in development. While work on this question is still in its preliminary stages, there is nevertheless increasing evidence that sensorimotor processes (defined here as any motor or proprioceptive process related to orofacial movements) affect developmental audiovisual speech processing. We suggest three areas on which to focus in future research: (i) the relation between audiovisual speech perception and sensorimotor processes at birth, (ii) the pathways through which sensorimotor processes interact with audiovisual speech processing in infancy, and (iii) developmental change in sensorimotor pathways as speech production emerges in childhood.